2009
DOI: 10.1038/aja.2009.81
|View full text |Cite
|
Sign up to set email alerts
|

Application of histone modification in the risk prediction of the biochemical recurrence after radical prostatectomy

Abstract: The role of histone modifications in the development and progression of cancer remains unclear. Here, we gave an investigation of the relationship between the various histone modifications and the risk prediction of the biochemical recurrence after radical prostatectomy (RP). Histone 3 lysine 4 dimethylation (H3K4diMe), trimethylation (H3K4triMe), lysine 36 trimethylation (H3K36triMe), histone 4 lysine 20 trimethylation (H4K20triMe) and acetylation of histome 3 lysine 9 (H3K9Ac) were evaluated using immnuohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…16 In fact, increased expression of MMP2 in cancer cells has been shown as a predictor of decreased prostate cancer disease-free survival. [17][18][19][20] MMPs are currently being evaluated for their 21 These patients underwent radical prostatectomy and did not receive any preoperative treatment. The histopathologic features of tumor specimens were reviewed by the Department of Pathology and classified according to the World Health Organization (WHO) criteria (NCCN Updates Prostate Cancer Guidelines in National Comprehensive Cancer Network, http:// www.nccn.org).…”
Section: Resultsmentioning
confidence: 99%
“…16 In fact, increased expression of MMP2 in cancer cells has been shown as a predictor of decreased prostate cancer disease-free survival. [17][18][19][20] MMPs are currently being evaluated for their 21 These patients underwent radical prostatectomy and did not receive any preoperative treatment. The histopathologic features of tumor specimens were reviewed by the Department of Pathology and classified according to the World Health Organization (WHO) criteria (NCCN Updates Prostate Cancer Guidelines in National Comprehensive Cancer Network, http:// www.nccn.org).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple mechanisms that alter the charge of histones and that are associated with increased chromatin opening and rate of transcription are well characterized. IHC analysis of global levels of mono-, di-and trimethylated H3K4 (H3K4me1/2/3), which are marks of active transcription, and acetylated H3K18 (H3K18ac), which marks TSS in actively transcribed genes or genes poised for transcription, have been shown to be independent predictors of recurrence in PC patients (Seligson et al 2005, Ellinger et al 2010, Zhou et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that the H3 trimethylation status at lysine 4 can predict the risk of BCR in low-grade PCa (Gleason score ≤ 6) after RP [ 17 ]. Therefore, UHRF1 might play an important role in tumourigenesis in the prostate.…”
Section: Introductionmentioning
confidence: 99%